Impact of a nurse-led programme on comorbidity management and impact of a patient self-assessment of disease activity on the management of rheumatoid arthritis: results of a prospective, multicentre, randomised, controlled trial (COMEDRA). Issue 9 (28th May 2014) - Dougados, Maxime; Soubrier, Martin; Perrodeau, Elodie; Gossec, Laure; Fayet, Françoise; Gilson, Mélanie; Cerato, Marie-Hélène; Pouplin, Sophie; Flipo, René-Marc; Chabrefy, Laurent; Mouterde, Gael; Euller-Ziegler, Liana; et al.
Abstract : Objectives: Rheumatoid arthritis (RA) patients are at an increased risk of developing comorbid conditions. A close monitoring of the disease targeting a status of low disease activity is associated with a better outcome. The aim of this trial was to evaluate the impact of a nurse-led programme on comorbidities and the impact of patient self-assessment of disease activity on the management of RA. Methods: We enrolled 970 patients (mean age 58 years, 79% women) in a prospective, randomised, controlled, open-label, 6-month trial. In the comorbidity group (n=482), the nurse checked comorbidities and sent the programme results to the attending physicians. In the self-assessment group (n=488), the nurse taught the patient how to calculate his/her Disease Activity Score which had to be reported on a booklet to be shared with the treating rheumatologist. The number of measures taken for comorbidities and the percentage of patients recording a change (initiation, switch or increased dose) in disease-modifying antirheumatic drugs (DMARDs) in the 6 months follow-up period of the study defined the outcomes of the trial. Results: The number of measures taken per patient was statistically higher in the comorbidity group: 4.54±2.08 versus 2.65±1.57 (p<0.001); incidence rate ratio: 1.78 (1.61–1.96) and DMARD therapy was changed more frequently in the self-assessment group: 17.2% versus 10.9% (OR=1.70 (1.17; 2.49), p=0.006). Conclusions: This study demonstrates the short-term benefit of a nurse-led programme on RA comorbidity management and the impact of patient self-assessment of disease activity on RA treatment intensification. Trial registration number: NCT #01315652.